P97 Uptake of the emergency salbutamol inhaler in North East England secondary schools following amendment of the Human Medicines Regulations. (12th November 2015) - Funston, W; Howard, SJ
Abstract : Introduction and objectives: As a result of amendments to The Human Medicines Regulations 2012, schools have been permitted since 1 st October 2014 to purchase salbutamol inhalers to be used by children diagnosed with asthma and prescribed an inhaler, where parents have given written permission for the emergency inhaler to be used. This regulatory change may represent a useful step in facilitating access to emergency asthma treatment in schools. This study provides the first published data on the number of schools that have availed of this new power, through an assessment of uptake of the emergency salbutamol inhaler in secondary schools in North East England. Methods: We compiled a list of all free-to attend schools within the 12 local authorities in North East England using listings on local authority websites. We limited our study to schools which served 16 year old mainstream pupils in order to aid interpretation of our results. Postal letters were sent to invite the included schools to complete a brief online or postal questionnaire asking if the school had an emergency salbutamol inhaler for use by pupils in an asthma emergency. Data was collected between November 2014 and May 2015. Results: Of 153 schools included in the study, 103 questionnaire responses were received. We excluded the response of 1 school due to lack of clarity. Of the remaining 102 responses, 45 (44%) indicated that the school had an emergency salbutamol inhaler available, while 57 (56%) indicated that the school did not have such an inhaler. The proportion of schools in which emergency salbutamol inhalers were available varied by local authority from 0% to 71%. Conclusions: Despite the change in legislation, 56% of schools included in this study did not possess an emergency salbutamol inhaler. More needs to be done to increase the level of uptake of the emergency salbutamol inhaler to enable schools to better respond to asthma emergencies.